4
$\begingroup$

Let $a,b,c,d$ be positive real numbers such that $a+b+c+d=4$. Prove that $$\frac{1}{ab}+\frac{1}{cd} \geq \frac{a^2+b^2+c^2+d^2}{2}$$ I write $$a^2+b^2+c^2+d^2=16-2\left(ab+cd+\left(a+b\right)\left(c+d\right)\right)$$. Then the inequality is equivalent to $$\frac{1}{ab}+\frac{1}{cd} +ab+cd+\left(a+b\right)\left(c+d\right) \geq 8$$ But now I don't know how to change $ab,cd$ into the forms of $a+b$ and $c+d$. Moreover, from the last inequality, we have $\frac{1}{ab}+\frac{1}{cd} \geq 4$, whereas $\left(a+b\right)\left(c+d\right) \leq 4$. I cannot handle this. Please help me.

$\endgroup$
3
$\begingroup$

Another way.

$$\frac{1}{ab}+\frac{1}{cd}-\frac{a^2+b^2+c^2+d^2}{2}=$$ $$=\left(\frac{1}{\sqrt{ab}}-\sqrt{ab}\right)^2+\left(\frac{1}{\sqrt{cd}}-\sqrt{cd}\right)^2+4-\left(ab+cd+\frac{a^2+b^2+c^2+d^2}{2}\right)=$$ $$=\left(\frac{1}{\sqrt{ab}}-\sqrt{ab}\right)^2+\left(\frac{1}{\sqrt{cd}}-\sqrt{cd}\right)^2+\frac{(a+b+c+d)^2}{4}-\frac{(a+b)^2+(c+d)^2}{2}=$$ $$=\left(\frac{1}{\sqrt{ab}}-\sqrt{ab}\right)^2+\left(\frac{1}{\sqrt{cd}}-\sqrt{cd}\right)^2-\frac{(a+b-c-d)^2}{4}.$$ Now, let $a+b\leq c+d$.

Thus, $0<a+b\leq2$ and by AM-GM $$\frac{1}{\sqrt{ab}}-\sqrt{ab}=\frac{1-ab}{\sqrt{ab}}\geq\frac{1-\left(\frac{a+b}{2}\right)^2}{\sqrt{ab}}\geq0.$$ Id est, it's enough to prove that: $$\frac{1}{\sqrt{ab}}-\sqrt{ab}\geq\frac{c+d-a-b}{2}$$ or $$1-ab\geq\sqrt{ab}(2-a-b)$$ or $$\sqrt{ab}(a+b)-2ab+ab-2\sqrt{ab}+1\geq0$$ or $$\sqrt{ab}(\sqrt{a}-\sqrt{b})^2+(\sqrt{ab}-1)^2\geq0$$ and we are done!

$\endgroup$
  • $\begingroup$ It has a little mistake but no problem. I got the idea. Thank you very much. $\endgroup$ – RuaSun Mar 21 at 7:18
  • $\begingroup$ @RuaSun You are welcome! I fixed. $\endgroup$ – Michael Rozenberg Mar 21 at 7:31
1
$\begingroup$

$ \frac{2}{a^2+b^2} \leq \frac{1}{ab} , \frac{2}{c^2+d^2} \leq \frac{1}{cd}$

$ \Rightarrow \frac{2(a^2+b^2+c^2+d^2)}{(a^2+b^2)(c^2+d^2)} \leq \frac{1}{ab} + \frac{1}{cd}$

$ \Rightarrow \frac{a^2+b^2+c^2+d^2}{2} \cdot (\frac{4}{(a^2+b^2)(c^2+d^2)} - 1)\leq \frac{1}{ab} + \frac{1}{cd} - \frac{a^2+b^2+c^2+d^2}{2}$

also, $ \frac{4}{(a^2+b^2)(c^2+d^2)} \geq \frac{1}{abcd} \geq 1 (\because 1 = (\frac{a+b+c+d}{4})^4 \geq abcd)$

$ \therefore 0 \leq \frac{a^2+b^2+c^2+d^2}{2} \cdot (\frac{4}{(a^2+b^2)(c^2+d^2)} - 1)\leq \frac{1}{ab} + \frac{1}{cd} - \frac{a^2+b^2+c^2+d^2}{2} , \frac{1}{ab} + \frac{1}{cd} \geq \frac{a^2+b^2+c^2+d^2}{2} $

$\endgroup$
  • $\begingroup$ I think it's wrong from the first line $\endgroup$ – RuaSun Mar 21 at 6:06
  • $\begingroup$ @MichaelRozenberg Thanks. I fix my answer $\endgroup$ – G.H.lee Mar 21 at 6:13
  • $\begingroup$ @G.H.lee Now, the first inequality in the fourth line is wrong. $\endgroup$ – Michael Rozenberg Mar 21 at 6:21
  • $\begingroup$ This approach cannot work, since $(a^2 +b^2)(c^2 + d^2) \le 4$ is false for $a+b+c+d=4$. For example, take $a, c$ close to $2$ and $b, d$ close to $0$; then $(a^2 + b^2)(c^2 + d^2)$ will be close to $16>4$. $\endgroup$ – Sameer Kailasa Mar 21 at 6:23
  • $\begingroup$ Oh, I made mistakes much... sorry .. I think my answer is completely wrong. So I'll delete my answer soon . I'm really sorry $\endgroup$ – G.H.lee Mar 21 at 6:27
1
$\begingroup$

Let $f(x)=\frac{1}{x(k-x)}-\frac{x^2+(k-x)^2}{2},$ where $0<x<k$.

Thus, $$f'(x)=-\frac{k-2x}{(kx-x^2)^2}-x-x+k=(2x-k)\left(\frac{1}{(kx-x^2)^2}-1\right)=$$ $$=\frac{(2x-k)(1-kx+x^2)(1+kx-x^2)}{(kx-x^2)^2}.$$ We see that $$1+kx-x^2=1+x(k-x)>0.$$ Consider two cases.

  1. $0<k\leq2.$

Thus, $$1-kx+x^2=\left(x-\frac{k}{2}\right)^2+1-\frac{k^2}{4}\geq0,$$ which says $$x_{min}=\frac{k}{2}$$ and $$f(x)\geq f\left(\frac{k}{2}\right)=\frac{4}{k^2}-\frac{k^2}{4}.$$ 2. $2<k<4.$

In this case we obtain $$\frac{k-\sqrt{k^2-4}}{2}<\frac{k}{2}<\frac{k+\sqrt{k^2-4}}{2},$$ which gives that $f$ gets a minimal value for $kx-x^2=1.$

Id est, $$f(x)\geq\frac{1}{1}-\frac{k^2-2}{2}=2-\frac{k^2}{2}.$$ Now, let $a+b=k\leq2.$

Thus, $c+d=4-k\geq2$ and $$\frac{1}{ab}+\frac{1}{cd}-\frac{a^2+b^2+c^2+d^2}{2}=\frac{1}{ab}-\frac{a^2+b^2}{2}+\frac{1}{cd}-\frac{c^2+d^2}{2}\geq$$ $$\geq\frac{4}{k^2}-\frac{k^2}{4}+2-\frac{(4-k)^2}{2}=\frac{(2-k)^3(3k+2)}{4k^2}\geq0$$ and we are done!

$\endgroup$
  • 1
    $\begingroup$ It looks like you may have a small typo in your definition of $f(x)$. $\endgroup$ – Sameer Kailasa Mar 21 at 6:14
  • $\begingroup$ @Sameer Kailasa Thank you! I fixed. $\endgroup$ – Michael Rozenberg Mar 21 at 6:18

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.